Conductas Internalizadas Y Externalizadas En Los Estudiantes De Básica Primaria De La Institución Educativa Distrital Unión Europea Sede B. (2014)
This research aims to describe the internalized and externalized behaviors present in the primary school students of the Institución Educativa Distrital Unión Europea. Initially we review theoretical based on child psychopathology from the dimensional focus set from Achenbach & Rescorla, and the description of internalizing and externalizing behaviors and mixed. From a sample of 93 students was held the application of the instrument Child Behavior Checklist - Format to parent Child Behavior Checklist (CBCL/6-18) ( CBCL , Achenbach & Rescorla , 2001) to identify the presence of internalized and externalized behaviors expressed by the child in the past 6 months. The methodology used in this research is descriptive, not experimental - cross. The investigation confirmed the existence of internalized and externalized behaviors in boys and girls, showing a high frequency of behaviors related to somatic complaints and aggressive behaviors in both genders.